(untitled) (Journal of Social Sciences Review, 2023)
Since governments around the globe are established to facilitate and provide a comfortable living standards to its citizens, they are working in various fields and their responsibilities are increasing day by day. In some areas, the governments cannot provide proper services to their citizens/people due to the lack of skills and sufficient budget. For this reason, it shares some of its activities with the private sector for a long period. This action is called Public-Private Partnerships (PPPs). This structure was first introduced to Afghanistan with the help of Dr. Ashraf Ghani in 2016 by announcing the PPPs Policy. Currently, in Afghanistan, there is very little or even no information available about the Effectiveness of the PPPs Project and programs. Hence, this research was conducted in order to explore the topic and investigate the critical success factors of PPPs Projects that were implemented in Afghanistan. The study is analytical and data are collected through a self-administered questionnaire and analyzed through SPSS and statistical tools. the sample size was determined by using Krejci and Morgan’s (1970) table. The findings of this research show that (6) success factors (Political support, Appropriate risk allocation, Good Governance, Availability of Financial Market and Transparency in the procurement process) out of (16) have a significant impact on PPPs project Implementation in Afghanistan.